Interaction of hydrogen-edged boron nitride flakes with lithium: boron nitride as a protecting layer for a lithium-ion battery and a spin-dependent photon emission device - Kheirabadi, Narjes; Shafiekhani, Azizollah (Nanotechnology, 2021)
The current rechargeable battery technologies have a failure in their performance at high pressure and temperature. In this article, we have brought theoretical insights on using boron nitride flakes as a protecting layer for a lithium-ion battery device and extended its application for a spin-dependent photon emission device. Hence, the electronic properties of pristine and lithium-doped hydrogen-edged boron nitride flakes have been studied by the first principle density functional theory calculations. In this study, we have discussed the stability, adsorption energies, bond lengths, electronic gaps, frontier molecular orbitals, the density of states, charge distributions, and dipole moments of pristine and lithium hydrogen-edged doped boron nitride flakes.